THE SUCCESSIVE CRISES IN YEMEN AND THEIR IMPACT ON MICRO, SMALL AND MEDIUM ENTERPRISES(MSMES) SECTOR - ALMAAMARI, OSAMAH AHMED; P, Vedava (International Journal of Research -GRANTHAALAYAH, 2020)
This study aimed to highlight the challenges and difficulties that face micro small and medium enterprises MSMEs on inhibiting from contributing to developing the Yemies economy and to know the impact of the successive crises and conflict on MSMEs. Through a review of the literature and previous studies in this regard, it was possible to summarize the most critical problems facing MSMEs in Yemen, which could be difficulties like getting funds, poor infrastructure, corruption, difficulties in securing raw materials, lack of skilled employees, and also difficulties to get Licensing and the absence of a specific SMEs authority.